2021
DOI: 10.1038/s41467-021-21389-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rhesus and cynomolgus macaques as an infection model for COVID-19

Abstract: A novel coronavirus, SARS-CoV-2, has been identified as the causative agent of the current COVID-19 pandemic. Animal models, and in particular non-human primates, are essential to understand the pathogenesis of emerging diseases and to assess the safety and efficacy of novel vaccines and therapeutics. Here, we show that SARS-CoV-2 replicates in the upper and lower respiratory tract and causes pulmonary lesions in both rhesus and cynomolgus macaques. Immune responses against SARS-CoV-2 are also similar in both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
166
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(182 citation statements)
references
References 53 publications
16
166
0
Order By: Relevance
“…Released virus then goes on to infect new epithelial cells with virus infection increasing exponentially in waves but becoming asynchronous. The decline in sgmRNA from Day 8/9 overlaps with IgG seroconversion and humoral immunity in both species 18 and follows similar kinetics to serology profiles measured in patients with COVID-19.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Released virus then goes on to infect new epithelial cells with virus infection increasing exponentially in waves but becoming asynchronous. The decline in sgmRNA from Day 8/9 overlaps with IgG seroconversion and humoral immunity in both species 18 and follows similar kinetics to serology profiles measured in patients with COVID-19.…”
Section: Discussionsupporting
confidence: 68%
“…This tends to be 5 to 6 days post-exposure. In the absence of a human challenge model, animal models can be used to study the kinetics of SARS-CoV-2 18, 19 . Two separate non-human primate models, cynomolgus and rhesus macaques, were established for the study of SARS-CoV-2 that mirrored disease in the majority of humans 18 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was primarily due to macaque availability at the time the study was conducted. However, this appears to have been both a strength [64] and weakness of the experimental design, as we found similar lung pathology in the cynomolgus macaque as well as similar patterns of BAL gene expression as the controls Rhesus subjects [72], and 5) we did not study the effects of adjuvant alone on SARS-Cov-2 infection in the Rhesus macaques. Previous experience with this microsphere CTL vaccine platform in a murine Ebola virus model has shown that adjuvant alone was not sufficient to confer protection against lethal virus challenge.…”
Section: Discussionmentioning
confidence: 95%